Image analysis of the eruptive positions of third molars and adjacent second molars as indicators of age evaluation in Thai patients - Phattaranant May Mahasantipiya (2018)
Purpose: This study was performed to determine the relationship between the stage of tooth eruption (both vertical and mesio-angular) and chronological age. Materials and Methods: Indirect digital panoramic radiographs were used to measure the distances from the dentinoenamel junction (DEJ) of the second molars to the occlusal plane of the second molar teeth and of the adjacent third molars in 264 Thai males and 437 Thai females using ImageJ software. The ratio of those distances was calculated by patient age, and the correlation coefficient of the ratio of the third molar length to the second molar length was calculated. Results: The correlation between the height of the vertically erupted upper third molar teeth and age was at the intermediate level. The age range of ≥15 to < 16 years was noted to be the range in which the correlation between the chronological age determined from the eruptional height and actual chronological age was statistically significant. The mean age of the female subjects, in which the position of the right upper third molar teeth was at or above the DEJ of the adjacent second molar but below one half of its coronal height was 19.9±2.6 years. That for the left side was 20.2±2.7 years. The mean ages of the male subjects were 20.1±3.3 years and 19.8±2.7 years for the right and left sides, respectively. Conclusion: It might be possible to predict chronological age from the eruption height of the wisdom teeth. © 2013 by Korean Academy of Oral and Maxillofacial Radiology.